Atuação fonoaudiológica na amamentação - Barbieri, Melanie Gomes (2023)
This study, of an exploratory and descriptive nature, aims to highlight the essential contribution of the speech therapist in the context of breastfeeding. The specific objectives include the analysis of reports of mothers facing breastfeeding challenges, the exploration of obstacles in breastfeeding management, the investigation of clinical conditions of mother and baby related to breastfeeding, and the evaluation of anatomical and functional aspects in the cases analyzed. The work is based on the analysis of data obtained through a survey carried out with mothers, and bibliography, emphasizing the importance of the speech therapist in the treatment and addressing different aspects of breastfeeding. The results emphasize the crucial relevance of the speech therapist in facing breastfeeding difficulties, highlighting how their intervention is essential to ensure effective feeding for the baby. Furthermore, the importance of continuous support for mothers to promote successful breastfeeding is highlighted